Sustainable large‐scale production of European flat oyster (Ostrea edulis) seed for ecological restoration and aquaculture: a review. (4th February 2021) - Colsoul, Bérenger; Boudry, Pierre; Pérez‐Parallé, María Luz; Bratoš Cetinić, Ana; Hugh‐Jones, Tristan; Arzul, Isabelle; Mérou, Nicolas; Wegner, Karl Mathias; Peter, Corina; Merk, Verena; Pogoda, Bernadette
Abstract: The conservation and active restoration of European flat oyster ( Ostrea edulis ) populations are a major focus of ecological restoration efforts to take advantage of the wide‐ranging ecosystem functions and services this species provides. Accordingly, additional and new demands for seed oysters have arisen. In commercial aquaculture (mariculture), the production of O. edulis is still largely based on natural seed collection. Considering the specific requirements, related to ecological restoration, such as the absence of pathogens and the preservation of high genetic diversity, the current supply is insufficient. Despite the development of breeding and controlled reproduction techniques for this species since the late 1930s, seed production today is mainly based on empirical concepts. Several of the issues that producers still face are already subjects of research; many others are still unanswered or even unaddressed. This review provides a summary of all available knowledge and technologies of O. edulis seed production. Furthermore, it provides a detailed reflection on implications for restoration, future challenges, open questions and it identifies relevant research topics for sustainable seed supply. The study covers the following aspects on (i) biology of the species, (ii) stressors – including pathogens and pollutants, (iii) genetics, (iv) history of production technologies, (v) seed production in polls, (vi) seed production in ponds and (vii) seed production in hatcheries. Future research needs on sex determinism, gametogenesis, cryopreservation, nutrition, selective breeding, pathogens and disease, and the development of reliable protocols for production are highlighted.